PERTUMBUHAN BIBIT GAHARU (Aquilaria malaccencis) DENGAN PEMBERIAN ZAT PENGATUR TUMBUH ASAL BAWANG MERAH - Aulia Putri Siregar; Elza Zuhry; Sampoerno ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Agarwood (Aquilaria malaccensis) is one character of forest plants that deliver really good quality with high economic value, because the forest contains a fragrant resin To overcome the scarcity of agarwoodgaharu cultivation needs to be exercised both in the forest or outside the woodland region.Referring to the cultivation of the required quality gaharu seedlings.The means to answer that is by giving PGR.Auxin found in plants are very few in number, and so it should be added exogenous auxin.One of the natural plant growth regulator that can be utilized in breeding agarwood was the juice of the onion. Juice of onion contains growth regulators, which have a role as Indol Acetic Acid. The experimentation was led at the experimental field of the Faculty of Agriculture, University of Riau. The experiment was conducted in December 2013 through the month of April 2014. This research was carried out experiments using a completely randomized design (CRD) consisting of five treatments, Z0: without PGR origin onion, Z1: PGR origin onion 5 ml / l of water, Z2: PGR origin onion 10 ml / l of water, Z3: PGR origin onion 15 ml / l of water and Z4: PGR origin onion 20 ml / l of water. The parameters measured were plant height, in the number of leaves , leaf area , leaf weight , stem circumference , number of branches , root volume , wet weight , dry weight and the ratio of the root crown. Giving PGR on agarwood seeds can increase the value of agarwood seedling growth, as determined in the parameters as height, increase in the number of leaves, leaf area, stem girth, fresh weight and dry weight.Offering a natural PGR derived from the onion with a concentration of 1.5 % and 2 % gave the best seedling growth Keyword : Onion, PGR, seedlings agarwood.